Analisis Marketing Pada Pizza Hut Delivery - Arief M. Iqbal; Elli Meida Panjaitan; Mona Parlinggoman Siregar; Shagy Reghita (Jurnal Teknik Informatika dan Sistem Informasi, 2015)
Pizza Hut and PHD actually are in the same company. Pizza Hut is focusing their business in restaurant, serve their customer directly on the table and also take away orders.Running their business in some period they bring new great idea to grab more markets and excellence service, they built PHD. PHD is focusing their business on delivery pizza. They didnt provide table and restaurant, they provide only small kiosk or outlet, accept all customers orders by phone or website and send them to customers address as mentioned on the orders list. They help customers well. They put easy way to order to their customers mind set. PHD make their customer happy and feel easy.Keywords: Restaurant, Small or Outlet, Great Idea, Phone or Website, Easy Way To Order.